The comprehensiveness of competing higher education sustainability assessments. Issue 3 (3rd May 2016) - Bullock, Graham; Wilder, Nicholas
Abstract : Purpose: The purpose of this paper is to analyze the comprehensiveness of competing higher education sustainability assessments. Higher education institutions (HEIs) have been increasingly communicating their sustainability commitments to the public. To assist the public in evaluating these claims, a broad range of actors have assessed the sustainability of HEIs. Design/methodology/approach: The paper uses an evaluation framework (the GRI-HE) consisting of criteria developed by the Global Reporting Initiative and the Association of University Leaders for a Sustainable Future to analyze the comprehensiveness of nine publicly-available frameworks that have been used to assess HEI sustainability. Findings: While finding that in general these assessments are not comprehensive and particularly lack coverage of the social and economic dimensions of sustainability, the paper identifies the Pacific Sustainability Index and Sustainability Tracking and Assessment Rating System (STARS) as the most comprehensive assessments in the sector. Research limitations/implications: This study does not assess the quality of the match to the GRI-HE's criteria, only whether they match to a reasonable degree. The analysis highlights areas where each HEI sustainability assessment framework can add criteria and improve their comprehensiveness and validity. Future research should explore the causes and relative importance of the gaps in these frameworks. Originality/value: The paper provides a valuable discussion and demonstration of the use of comprehensiveness as a proxy metric for the validity of sustainability assessments. This analysis is the first detailed, comprehensive and transparent analysis of HEI sustainability assessments based on a broad-based and widely accepted set of criteria.